Nucleoredoxin Gene TaNRX1 Positively Regulates Drought Tolerance in Transgenic Wheat (Triticum aestivum L.) - Zhang, Yunrui; Zhou, Jianfei; Wei, Fan; Song, Tianqi; Yu, Yang; Yu, Ming; Fan, Qiru; Yang, Yanning; Xue, Gang; Zhang, Xiaoke (Frontiers in Plant Science, 2021)
Drought is the main abiotic stress factor limiting the growth and yield of wheat (Triticum aestivum L.). Therefore, improving wheat tolerance to drought stress is essential for maintaining yield. Previous studies have reported on the important role of TaNRX1 in conferring drought stress tolerance. Therefore, to elucidate the regulation mechanism by which TaNRX1 confers drought resistance in wheat, we generated TaNRX1 overexpression (OE) and RNA interference (RNAi) wheat lines. The results showed that the tolerance of the OE lines to drought stress were significantly enhanced. The survival rate, leaf chlorophyll, proline, soluble sugar content, and activities of the antioxidant enzymes (catalase, superoxide dismutase, and peroxidase) of the OE lines were higher than those of the wild type (WT); however, the relative electrical conductivity and malondialdehyde, hydrogen peroxide, and superoxide anion levels of the OE lines were lower than those of the WT; the RNAi lines showed the opposite results. RNA-seq results showed that the common differentially expressed genes of TaNRX1 OE and RNAi lines, before and after drought stress, were mainly distributed in the plant–pathogen interaction, plant hormone signal transduction, phenylpropane biosynthesis, starch and sucrose metabolism, and carbon metabolism pathways and were related to the transcription factors, including WRKY, MYB, and bHLH families. This study suggests that TaNRX1 positively regulates drought stress tolerance in wheat.